The Wicked Problems of Durability: Rebound Effects and Textile Illiteracy in Circular Policy - Richardy, Jesper; Skjold, Else; Skødt, Trine (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
This paper takes its starting point from the EU Strategy for Sustainable and Circular Textiles which proposes that: “Increased durability will enable consumers to use clothing for longer and at the same time support circular business models such as reuse, renting and repair, take-back services and second-hand retail, in a way that creates cost-saving opportunities to citizens” (European Commission, 2022). While this statement positions durability as a cornerstone of circularity, and assumes that increasing product lifespan will naturally align with economic, environmental, and social benefits. This paper challenges that assumption by investigating the rebound effects and ’wicked problems’ associated with durability as a driver for circular business models. By applying Rittel and Webber’s (Rittel & Webber, 1973) framework, the analysis addresses multiple levels of root problems that complicate this narrative. Empirical data from two ongoing studies will be presented to illustrate how gaps in textile literacy—both in industry and among consumers—undermine the technocratic assessments underpinning EU strategies. These studies highlight how the erosion of textile knowledge over recent decades has left terms like "durability" and "circularity" poorly understood and misapplied. The concluding argument of this paper is that this lack of historical and practical textile knowledge within EU policy-making constitutes a rebound effect in itself. Without a deeper, more nuanced understanding of what durability and circularity entail and how they can be practiced, the strategy risks failing to achieve its intended positive impacts.